Semiochemicals-baited traps for detecting and estimating the population density of Scyphophorus acupunctatus Gyllenhal (Coleoptera: Dryopthoridae), in agaves, in Tlaquiltenango, Morelos - Laura Fabiola Cruz-Jardón (Acta Zoológica Mexicana (nueva serie), 2018)
Scyphophorus acupunctatus Gyllenhal (Coleoptera: Dryophthoridae) is an important pest in agaves, and is the main pest of agaves in Morelos, also this is the first time that the population density of this weevil was sampled in agave plantations in Morelos state using pheromone-baited traps.